Urban Regeneration – Strategies of Shrinking Cities in Eastern Germany - Kühn, Manfred; Liebmann, Heike (DIE ERDE – Journal of the Geographical Society of Berlin, 2012)
This contribution is meant to contrast the often negative images and scenarios of demographic change in eastern German cities by a more differentiated picture, by discussing regeneration processes running parallel – and sometimes even opposite – to shrinking. In this context, the regeneration of cities is understood as a complex process including demographic, socio-economic and physical dimensions. In the first part of the article the term will be discussed and some conceptional aspects will be presented. The second part will present evidence for a differentiated development of mediumsized towns. In the third part, we will present the hypothesis that strategies of urban development influence regeneration processes. This hypothesis will be evaluated by the examples of three cities with different regeneration approaches: Brandenburg an der Havel, Görlitz and Greifswald. Finally we will draw some general conclusions on urban development policy in eastern Germany.